2020
DOI: 10.1002/tsm2.197
|View full text |Cite
|
Sign up to set email alerts
|

Concentric versus eccentric training: Effect on muscle strength, regional morphology, and architecture

Abstract: Skeletal muscles produce force by shortening (concentric, CON), lengthening (eccentric, ECC), or contracting isometrically, but the two actions differ in the mechanisms by which force is generated. 1 Eccentric actions during maximal voluntary isokinetic exercise usually result in lower muscle activity than CON actions, 2 but the maximal attainable forces are considerably higher. 1 During ECC actions, titin, a protein spanning half the sarcomere, contributes to active stress when the muscle lengthens, acting as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Additionally, the hand-search of references revealed 17 records, of which 6 were included in the systematic search of In the end a total of 18 studies met all inclusion criteria (Blazevich et al, 2007;Duclay et al, 2009;Potier et al, 2009;Guilhem et al, 2013;Franchi et al, 2014;Sharifnezhad et al, 2014;Coratella et al, 2015;Timmins et al, 2016b;Bourne et al, 2017;Seymore et al, 2017;Abdel-Aziem et al, 2018;Kay et al, 2018;Ribeiro-Alvares et al, 2018;Duhig et al, 2019;Delvaux et al, 2020;Marušič et al, 2020;Benford et al, 2021;Uysal et al, 2021) and were included in this systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the hand-search of references revealed 17 records, of which 6 were included in the systematic search of In the end a total of 18 studies met all inclusion criteria (Blazevich et al, 2007;Duclay et al, 2009;Potier et al, 2009;Guilhem et al, 2013;Franchi et al, 2014;Sharifnezhad et al, 2014;Coratella et al, 2015;Timmins et al, 2016b;Bourne et al, 2017;Seymore et al, 2017;Abdel-Aziem et al, 2018;Kay et al, 2018;Ribeiro-Alvares et al, 2018;Duhig et al, 2019;Delvaux et al, 2020;Marušič et al, 2020;Benford et al, 2021;Uysal et al, 2021) and were included in this systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…Samples' mean age ranged from 19 (Kay et al, 2018) to 28 years (Potier et al, 2009;Seymore et al, 2017). 11 of the 18 studies included males only (Duclay et al, 2009;Guilhem et al, 2013;Franchi et al, 2014;Coratella et al, 2015;Timmins et al, 2016b;Bourne et al, 2017;Abdel-Aziem et al, 2018;Duhig et al, 2019;Delvaux et al, 2020;Benford et al, 2021;Uysal et al, 2021). 15 studies examined FL changes by ultrasound (Blazevich et al, 2007;Duclay et al, 2009;Potier et al, 2009;Guilhem et al, 2013;Franchi et al, 2014;Sharifnezhad et al, 2014;Coratella et al, 2015;Timmins et al, 2016b;Bourne et al, 2017;Seymore et al, 2017;Kay et al, 2018;Ribeiro-Alvares et al, 2018;Duhig et al, 2019;Marušič et al, 2020;Benford et al, 2021).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As muscle remodelling processes appear to be related to the amount of stress and strain applied onto the muscle 24 , it is also possible that muscle strain may be heterogeneous across different regions of the same muscle 14,25 implying that morphological, structural and even molecular adaptations due to eccentric training are non-uniform within the muscle 3,17 . For example, in vivo measures of sarcomere length in the human tibialis anterior muscle have shown that sarcomeres are longer in the distal compared to the proximal region, despite fibres being of similar length 27 .…”
Section: Introductionmentioning
confidence: 99%